ANALISIS STRATEGI PENYALURAN DANA ZAKAT UNTUK PENGENTASAN KEMISKINAN (STUDI PADA BAZNAS KABUPATEN SAROLANGUN) - Muhammad Afiq Safaruddin Nur; A.A Miftah; Ogi Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to find out whether the profit sharing for land Zakat is a source of funds for the welfare of the people, especially to alleviate poverty and eliminate social inequality. This empowerment program through the distribution of productive zakat must be prioritized. The meaning of empowerment in the broadest sense is to make partners independent, so that partners in this case mustahik are not always dependent on amil. The zakat distribution strategy carried out by BAZNAS Sarolangun Regency which uses the budgeted zakat surplus model has succeeded in increasing the mustahik's income and economy. The productive zakat distribution mechanism is in accordance with Law no. 23 of 2011 concerning Zakat Management but it has not been fully maximized. The distribution of zakat at BAZNAS Sarolangun Regency is also in accordance with the areas that have been determined.